Analisis Restrukturisasi Piutang Kredit Pemilikan Rumah Pada Bank BTN Kc Sukabumi - Averilliana, Carissa; Kartini, Tina; Martaseli, Evi (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
The purpose of this study is to find out how the credit/receivable restructuring process at Bank BTN Kc Sukabumi is. The method used in this study is a qualitative descriptive method using both methods of data collection. Observations of the problem in the form of interviews were examined both as primary and secondary sources. Based on the research results obtained, the process of restructuring mortgage credit/receivables at Bank BTN KC Sukabum was carried out by dividing it into several patterns, namely there were 3 patterns, arrears to increase current installments, addition of time period, new installment period. After all that has been done, along with the submission process, there is a form that must be filled in, the conditions are such as KTP, NPWP, after that if the files are ready the bank will process the Pia Ilon tool/system at the bank to see what the results are displayed, later there is an addendum (additional letter of agreement) regarding the restructuring, whether approved or not, and if approved, which of the three drafts is approved.